Prevalence of acute mountain sickness in the Eastern Alps - Mairer, K.; Wille, M.; Bucher, T.; Burtscher, M. (High Altitude Medicine & Biology, 2009)
Little information is available on the prevalence of acute mountain sickness (AMS) in the Eastern Alps compared with the Western Alps. Because of differences regarding the populations of mountaineers, we hypothesized that the prevalence differs between the Eastern and Western Alps. Thus, we determined the prevalence and risk factors of AMS at four different altitudes in the Eastern Alps of Austria. Four hundred and thirty-one recreational hikers were studied using questionnaires on the morning of their first night at high altitude. A diagnosis of AMS was based on a Lake Louise Score =4, the presence of headache, and at least one additional symptom. Overall 16.2% of the subjects met the criteria for AMS, and the prevalence of AMS increased significantly with altitude (2200m: 6.9%; 2500m: 9.1%; 2800m: 17.4%; 3500m: 38.0%). Heavy perceived exertion, a history of migraine, the absolute altitude reached, little mountaineering experience, and inadequate water intake (=2L) were independent AMS risk factors. The reported altitude-related AMS prevalence in the Western Alps is 4% to 8% lower compared with that found in this study for the Eastern Alps. In conclusion, the prevalence of AMS is higher in the tourist population of the Eastern Alps compared to the more experienced mountaineers of the Western Alps. Consideration of easily modifiable risk factors such as individual exertion and water intake could markedly reduce AMS and contribute to the enjoyment of mountaineering.